Pengetahuan Mahasiswa Mengenai Kesiapsiagaan Bencana di Universitas Binawan Jakarta - Harizza Pertiwi; Zakiyah; Intan Parulian (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Indonesia is a country that is very prone to disasters. Disasters that have occurred repeatedly in Indonesia have resulted in significant loss of both economy and lives. Thus, adequate preparedness measures are needed to minimize these losses. Students as agents of change need to have good knowledge about disaster preparedness so that they can provide positive changes in society related to disaster preparedness. The purpose of this study is to analyze the level of knowledge of Binawan University students regarding disaster preparedness. The method used in this research was descriptive analytic. The sample in this study were Binawan University students who met the inclusion criteria set by the researcher. Purposive sampling technique was used to determine the number of participants needed. Data analysis was performed using univariate analysis which was carried out on respondents’ characteristics (age and gender) and knowledge variable using percentage and proportion measures. The results show that a number of 207 (65.1%) respondents had low level of knowledge about disaster preparedness. The conclusion obtained from this study is that Binawan University students do not yet have a good level of knowledge which may be due to the unevenness of integrating curriculum regarding disaster preparedness in all majors. The suggestion that researcher can propose is to integrate the disaster preparedness curriculum in all majors so that all students can have the opportunity to increase their knowledge regarding disaster preparedness. The result of this research can also serve as a background for conducting disaster-related training for students